Superficial Spreading Cervical Squamous Cell Carcinoma to Endometrium: A Rare Case Report - Limanto, Jennifer Jesse; Prasetiyo, Patricia Diana; Djohansjah, Alexy Oktoman; Chandra, Shally (Fakultas Kedokteran Universitas Pelita Harapan, 2024)
Introduction: Squamous cell carcinoma (SCC) was the most common variant of cervical cancer with metastases potential to many organs, commonly parametrium and vagina, but in a rare condition can also spread to endometrium. Further evaluations are needed since superficial spreading of cervical SCC are related to poorer outcomes. Case Presentation: A 62 y.o, post-menstrual, P3A0 women came with complaint of vaginal discharged mixed with blood since 6 months ago. Pap smear result suggestive of malignancy so the patient undergo guided biopsy from endocervix that revealed finding similar to carcinoma intraepithelial (CIN) 3. The patient underwent TAH-BSO operation. Microscopic examination from cervix showed tumor cell with round nuclei, prominent nucleoli, pleomorphic, hyperchromatic, increased nuclear-cytoplasm ratio in whole epithelial layer. Microscopic examination from endometrium showed epithelial squamous cell proliferation in almost 98% endometrial tissue and atypical cell nuclei, consistent with tumor founded in cervix. The final diagnosis was superficial endometrial spreading SCC with moderate differentiation. Immunohistochemistry (IHC) assay with p16 showed positive result in endometrium. Patient then consulted to gynecologist – oncology specialist for further treatment and evaluation. Conclusion: Superficial spreading of cervical SCC to endometrium was a rare finding. Detection of SCC in endocervix can be considered as predictor for proximal spreading of cervical SCC so further examination like endometrial curretage are suggested to assist the early detection. IHC assay with p16 resulted positive in our patient suggesting that endometrial SCC in this patient was correlated with HPV infection that commonly find in cervical cancer.